Organização de processos de trabalho fonoaudiológicos no contexto hospitalar: uma experiência em hospital privado - Duarte, Maria José de Freitas (2015)
This paper analyzes the process organization of speech pathology therapy work in a private general hospital in the city of São Paulo, considering the external evaluations to which this applies systematically and periodically, to be known: National Accreditation Organization (ONA), Joint Commission and Canadian Council on Health Services Accreditation (CCHSA). The research had two complementary objectives: characterize the demand for speech therapy during the years of 2013 and 2014; and to present the workflow and interaction of speech therapy in interdisciplinary hospital health team to attend such demand. The dimensions were not investigated yet by brazilian speech therapy, and it gives a new sense for the study. The text is organized in 4 parts: conceptual introduction, method, results presentation, discussion and conclusion. The first is a panoramic about evaluation and the search for qualification of hospital attention in Brazil; presents the hospital accreditation process, especially those with which the reaserched Hospital voluntarily is committed to; and contextualizes the speech therapy in this universe. Method: the research is described and configured in two times: 1- search and presentation of the workflow and processes built by speech therapy, in partnership with the hospital interdisciplinary team, to take care of evaluated and rehabilitaded patients; 2- search and characterization of the demand attended by speech therapy in 2013 and 2014. The databases of the research were: Hospital Information System (Tasy); registers of speech therapy department; the perception and reading of the researcher (author) because of the experience at referred hospital. Results presentation: due to the essence of speech pathology therapy work at the hospital, we can mention evaluation and rehabilitation of dysphagy, with flow characterization, organization and construction of procedures or operational standard protocols (POPs), validated by Accreditation Agencies and by Hospital Management. Information related to demand are treated as descritive statistics. The workflow is presented in activities´ diagram and/or relationship of speech therapy and other professional sectors and categories at the Hospital. The final part, dedicated to results discussion and research conclusions, indicated potentialities and challenges to speech pathology therapy workflow and processes at the Hospital under external evaluation made by referred agencies